ANALISIS KEKUATAN SAMBUNGAN LAS LISTRIK BUSUR MANUAL (SMAW) PADA BAJA KARBON RENDAH DENGAN VARIASI ARUS AMPERE 120A, 125A DAN 130A - Abdul Majid Rahman; Amri Hidayat; Fadhli Dzil Ikram; Aldrin Aldrin (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2023)
The strength of the welded joint is greatly influenced by one of the welding parameters, namely the amount of welding current. Determination of the amount of current in metal joining using arc welding. To get a good connection quality, it is necessary to determine the right current. The purpose of this study was to determine the tensile strength and hardness values ??of ASTM A36 low carbon steel after being welded using E 7018 electrodes with several current variations. This research is an experimental study that analyzes the tensile strength and hardness values ??of welding ASTM A36 low carbon steel using variations of three welding currents, namely 120A, 125A and 130A. The specimens used came from a material in the form of low carbon steel ASTM A36 with a thickness of 10 mm which had been welded using an E 7018 electrode. The results of the research that had been carried out showed that the average value of the tensile strength using a current of 120A was 510.49 (N/ mm²). The 125A current is 437.15 (N/mm²), and the 130A current is 258.72 (N/mm²). While the average hardness value of the specimen using a current of 120A is 78.83 HRB, at a current of 125A it is 89.81 HRB, and a current of 130A is 78.90 HRB. The results of welding with the E 7018 electrode have an ideal tensile strength with a welding current of 120A, while the highest hardness value is found at a current of 125A.